Diabetes weight loss-- week by week : a safe, effective method for losing weight and improving your health - Weisenberger, Jill. (Alexandria : American Diabetes Association, 2012)
'Diabetes Weight Loss-Week by Week guides the overweight person with diabetes through the steps to lasting weight loss, better health, and perhaps even improved blood glucose control. The reader will learn to set reasonable goals; make better choices in restaurants, the grocery store, and the kitchen; self-monitor food intake, activity, and progress; read food labels; distinguish appetite from hunger; navigate a restaurant menu or buffet; examine motivation; and more. More than 23 million adult Americans have some form of diabetes, and more than two-thirds of the adults with type 2 diabetes are significantly overweight or obese. Many of these individuals feel that controlling blood glucose and weight are conflicting goals and that they must choose one over the other. This books dispels that myth by educating the reader about the benefits of good nutrition and weight loss. Losing weight may improve blood glucose; blood pressure; cholesterol and triglyceride levels; increase mobility, comfort, and confidence; reduce the risk for heart disease; and improve overall quality of life. Many overweight people have tried unsuccessfully to lose weight one or more times. Frequently, dieters lose weight, only to regain it within months. With this book's week-by-week approach and emphasis on incremental changes, the reader will increasingly gain the knowledge, skills, and confidence required for permanent change. Throughout the book, readers will learn from the triumphs of others by reading their brief stories. A handful of recipes will guide the reader to making changes in the kitchen. Among many other lessons and skills, readers will: Record and review their food intakePractice setting achievable goalsIdentify the benefits and sacrifices of changing eating and physical activity routinesLearn to deal with friends and family members who sabotage lifestyle change effortsLearn to recover from dietary setbacks and indiscretionsDiscover mindful eatingIdentify filling
'This book will help the reader learn that weight loss is about skill, not willpower. Using knowledge, strategies, skills, self-confidence, and feedback, the reader learns to take small steps while trimming down, and taking care of diabetes at the same time'--
foodsDecrease portionsIdentify and avoid trigger foods and situationsPrepare healthful foodsCreate positive, supportive situationsGradually increase physical activityAvoid hypoglycemia while losing weight'--
'A safe, effective method for losing weight and improving your health'--Cover.
Includes bibliographical references and index.
Keywords: Diabetes -- Diet therapy; Diabetes -- Exercise therapy